Perbedaan Pengetahuan Antara Sebelum Dan Sesudah Pelatihan Pengukuran Status Gizi Balita Pada Kader Posyandu Desa Gunungtiga, Kecamatan Ulubelu, Kabupaten Tanggamus, Lampung - Rika Rahmawati; Fitria Saftarina (Majority, 2020)
In 2016 Tanggamus Regency had 70 cases of infant mortality, under-fives with malnutrition 1,371 cases (3.31%), and 1 case of malnutrition, and the coverage of community participation in under-fives growth monitoring was 75.6% . However , uneven distribution of health workers and low knowledge of health cadres about measuring the nutritional status of children, so the coverage of nutritional status is still low. This study uses the quassy experimental method with the design of one group pretest-posttest design. The sampling technique is total sampling. The research was conducted from April to July 2018, located in Gunungtiga Village, Ulubelu District, Tanggamus Regency, Lampung. The subjects that were obtained were 18 Posyandu cadres. The result of the median value of the knowledge pre-test is 30, while the median value of the post-test knowledge is 80. The results of the bivariate analysis p = 0,000. There were significant differences between before and after training in measuring the nutritional status of children under five to the knowledge of Posyandu cadres in Gunungtiga Village.